The role of planning in new urban settlements: The case of Nyagatare in post-conflict Rwanda - Gregory, Carmel (School of Architecture, Planning and Geomatics, 2014)
The study of urban planning in post-conflict settlements is an area of research that has not yet been thoroughly explored. Yet planning occupies a unique position at the interface between communities, the state, and the physical environment, and is strategically located to deal with many common long-term impacts of conflict in societies. As such it deserves greater attention and consideration for the contribution it can make to reconstruction and peace-building. This study interrogates the notion of post-conflict urban planning within the case of Nyagatare, Rwanda, a town that has been almost entirely settled by returned refugees and post-conflict migrants since the 1994 genocide in Rwanda. The town has seen rapid population growth and this year was designated as one of six secondary cities selected for focused investment and further population growth: this post-conflict rise from village to secondary city in less than two decades is unprecedented in Rwanda. Field research was conducted and qualitative data collected through interviews in the field. Further information and analysis came from NGO and government reports, as well as drawing from work by previous researchers. The research found that there are still several lasting impacts from conflict, including disputes over land, weak civil society, weak local democratic process, lack of social cohesion and high rates of social distrust, and suspicious attitudes towards the state. Nyagatare is likely to be a hotspot for resettlement, voluntary or otherwise, of returning refugees who have lost their protected status under the recent invocation of the refugee Cessation Clause by the Government of Rwanda and the UNHCR. Post-conflict impacts are thus likely to be compounded with ongoing influxes of population, both through refugee resettlement and domestic migration. Yet current spatial planning fails to address these impacts of conflict as well as failing to appropriately anticipate the needs of future populations of the town. This study thus seeks to propose an alternative framework for planning that directly addresses the lasting impacts of conflict. Recommendations for planning include adapting co-production and strategic spatial planning to the local context, incorporating traditional mediation structures to allow for a safe venue for engaging communities. Focused strategic interventions, rather than a master plan, are recommended in order to allow for flexibility and uncertainty as the town grows and society stabilises.